VIOLENCE AND PAGANISM IN THE EARLY CAROLINGIAN FRANKISH WORLD: REPRESENTATIONS OF THE GERMANIC ALTERITY (8TH CENTURY) - Perl Garrido, Jonathan (Revista de Historia Social y de las Mentalidades, 2016)
The paper adressesone of the aspects on the issue  of the construction of the representations of the  otherness in the early Carolingian period. This  otherness is considered to be identified with the  people that were not included in the Frankish  political unit nor in the Christian religious unit,  established in the north-eastern regions of the  Frankish kingdom of Austrasia, mainly Saxons  and Frisians. In the definition of these people as  “the Others”, religious and moral criteria played  a fundamental role. From historiographical,  hagiographical, epistolary and legal sources, a  review is made on the wayin which the pagans  were represented by the Christian authors, as  characteristically violents towards Christendom  (and the Frankish order), from which they are  qualified inside the concept of “barbarians”. It is  propossed and shown that the use of the resource  to physical violence from the barbarians varies  according to specific contexts in which the  sources were produced, especially in terms of the  contemporary development of the processes of  evangelization and conquest of the forementioned  regions, and those processes within the Frankish  kingdom, related to the taking and maintenance  of the power in the realm by the Carolingians
Keywords: Otherness; Evangelization; Violence; Saxons; Paganism; Barbarism